Evaluation of Museum Staff Development in Government Museums in the DKI Jakarta Province - Panjaitan, Dame Rohana Gustiani; Rajab, Ridwan; Asropi, Asropi (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this research is to improve the role and function of the Directorate of Development of Cultural Personnel and Institutions in supporting the development of cultural personnel and institutions that are right on target for Museum Curator technical personnel at Government Museums in DKI Jakarta Province, to find out the targeted coaching model for Museum Curator technical personnel at Government Museums in DKI Jakarta Province, and to increase the effectiveness of coaching programs for Museum Curator technical personnel at Government Museums in DKI Jakarta Province. The research method used is descriptive research with a qualitative approach. The results showed that the technical guidance activities for museum curators facilitated by the Directorate of Personnel Development and Cultural Institutions are activities that will equip museum curators in increasing their competence. The evaluation of technical guidance is carried out with the CIPP model which identifies the background of the activity, objectives, facilitators/organizers, instructors, participants, activity schedules, evaluation reports, and museum curator certification.